ADOPTION OF CLIMATE-SMART ADAPTATION STRATEGIES AMONG FARMERS IN ADAVI LOCAL GOVERNMENT AREA OF KOGI STATE - Edoka, M. H.; Adiel, K. B.; Ibrahim, F. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study evaluated the adoption of climate-smart agricultural strategies by farmers in Adavi Local Government Area (LGA) of Kogi State, Nigeria. A multi-stage sampling technique was adopted to select 150 farmers from the LGA. Structured questionnaire was developed and distributed to the farmers for data collection. Data collected were analyzed through the use of descriptive (frequency distribution, percentages and means) and inferential statistics (Logit Regression Model). The results showed that majority (78.7%) of the respondents were males with a mean age of 27 years. Majority (62.0%) of respondents were married having a mean household size of seven persons. More than half (58.0%) of the farmers had secondary education, operating on a mean farm size of about 5ha. Sixty percent of the farmers had extension contact, while 68.0% did not belong to any cooperative society. Agricultural practices (83.0%), deforestation (77.3%), and house and road constructions (72.0%) were identified as major causes of climate change. While low crop yield (85.3%), rise in atmospheric temperature (81.3%), and land degradation (76.7%) were identified as major effects of climate change. Climate-smart agricultural strategies adopted in response to these changes in climate included; use of tolerant crop varieties (88.0%), bush fallow (84.0%), and use of organic manure (77.3%). Logistics results reveal that extension contact (B= 3.389; P= 0.001), educational level (B = 3.360; P = 0.050) and farm size (B = 4.065; P= 0.075) were statistically significant factors influencing the adoption of CSAPs by farmers. Constraints such as inadequate fund (Mean=2.6), poor extension contact (Mean=2.5), and high cost of adaptation facilities (Mean = 2.4) affect the adoption of climate-smart adaptation strategies by farmers. The study recommended that; government should provide soft loans to farmers to enable them access CSA facilities, extension-farmer linkage should be strengthened to render prompt assistance and guidance to farmers.